Liver-boosting potential: chicory compound-mediated silver nanoparticles for hepatoprotection—biochemical and histopathological insights - Siddiqa, Ayesha; Qureshi, Rahmatullah; Raja, Naveed Iqbal; Khan, Imtiaz Ahmed; Ahmad, Muhammad Zishan; Rafique, Shaista; Ali, Amir; Ahmad, Ajaz; Kaushik, Prashant (Frontiers in Pharmacology, 2024)
Background: Liver disease is a serious health concern in today’s world, posing a challenge to both healthcare providers and pharmaceutical companies. Most synthetic drugs and chemicals cause liver damage accounting for approximately 10% of acute hepatitis and 50% of acute liver failure. Purpose: The present study aimed to evaluate the hepato-protective activity of an extract of chicory formulation assisted by silver nanoparticles against carbon tetra chloride (CCl4)-induced hepatic damage in rat’s liver. Methods: Rats of the Wistar strain (Rattus norvegicus) were used to test the in vivo hepato-protective efficacy at various doses. Rats were randomly divided into nine groups, each containing six rats. The groups were as follows: first group (control), second group (CCl4), third group, silymarin (20 mg/kg of body weight), fourth group (CCl4+chicory) (1.75 mg/kg of b. wt), fifth group (CCl4 + chicory at the dose of 2.35 mg/kg), sixth group (CCl4 + chicory of 3.25 mg/kg), seventh group (CCl4 +AgNPs 1.75 mg/kg of b. wt.), eighth group (CCl4 + AgNPs 2.35 mg/kg of body weight), and ninth group (CCl4 + AgNPs 3.25 mg/kg of b. wt.). Blood samples were taken 24 h after the last administration (i.e., 30th day). The blood samples were analyzed for different serum enzymes such as ALP (alkaline phosphatase), ALT (alanine transaminase), bilirubin (Blr), triglyceride, and cholesterol. Histology liver sections were performed. Results: Treatment with AgNPs and chicory extract showed significant hepato-protective activity in a dose-dependent manner. In three doses, the chicory extract at a rate of 3.25 mg/kg of body weight significantly reduced elevated levels of biochemical markers in comparison to CCl4-intoxicated rats. Histology of the liver sections from CCl4-treated rats revealed inflammation of hepatocytes, necrosis, cytoplasmic degeneration, vacuolization, and a deformed central vein. The chicory formulation extract exhibited a remarkable recovery percentage in the liver architecture that was higher than the drug (i.e., silymarin). While treatment with AgNPs also repaired the degenerative changes and restored the normal form of the liver, chicory formulation extract possessed more hepato-protective potential as compared to AgNPs by regulating biochemical and histo-pathological parameters. Conclusion: This study can be used as confirmation of the hepato-protective potential of chicory compounds for possible use in the development programs of drugs to treat liver diseases.